Discovering the Wisdom of the Orang Asli Traditional Dwellings: Typologies Formation Through Physical Characteristics - Noor Hanita Abdul Majid; Mohd Afiq Rosali (Engineering Proceedings)
The architecture of the Orang Asli (OA) in Peninsular Malaysia has always been disregarded in studies of the indigenous people. This study is a venture towards recognizing and classifying the OA dwellings into typologies by outlining the salient characteristics of the physical form for further studies about the OA traditional dwellings. Data are collected through field measurements, interviews, and visual recordings of the identified case studies. Typologies of the OA are formed by analyzing the basic shapes and architectural characteristics, salient architectural features, and materials. This study found that the OA dwellings have sustainable and unique attributes to the sub-ethnicities. The typology classification is the plan and roof form (roof slope degrees), height of the floor from the ground level, opening and geometry, and material used for construction.